2017
DOI: 10.1016/j.mito.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein 2 and metabolic diseases

Abstract: Mitochondria are fascinating organelles involved in various cellular-metabolic activities that are integral for mammalian development. Although they perform diverse, yet interconnected functions, mitochondria are remarkably regulated by complex signaling networks. Therefore, it is not surprising that mitochondrial dysfunction is involved in plethora of diseases, including neurodegenerative and metabolic disorders. One of the many factors that lead to mitochondrial-associated metabolic diseases is the uncouplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 98 publications
3
49
1
Order By: Relevance
“…We have previously demonstrated that UCP2 is overexpressing at the protein level in several human cancers . The increased levels of UCP2 have been linked to enhanced cell proliferation and tumorigenicity . Furthermore, our results showed that UCP2 overexpression promoted skin tumorigenesis via altering glucose and lipid metabolism, and the key regulators of metabolic processes .…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…We have previously demonstrated that UCP2 is overexpressing at the protein level in several human cancers . The increased levels of UCP2 have been linked to enhanced cell proliferation and tumorigenicity . Furthermore, our results showed that UCP2 overexpression promoted skin tumorigenesis via altering glucose and lipid metabolism, and the key regulators of metabolic processes .…”
Section: Introductionsupporting
confidence: 51%
“…[22] The increased levels of UCP2 have been linked to enhanced cell proliferation and tumorigenicity. [19,23] Furthermore, our results showed that UCP2 overexpression promoted skin tumorigenesis via altering glucose and lipid metabolism, and the key regulators of metabolic processes. [24,25] As such, UCP2 is thought to be a crucial player in the cascade of molecular and metabolic events associated with carcinogenesis.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…On the other hand, one study on 268 obese and 185 nonobese children and adolescents showed that the ins allele of the UCP2 45-bp D/I polymorphism may contribute to low HDL cholesterolemia [35]. Besides, various studies have presented UCP-2 45-bp D/I polymorphism association with higher degree of obesity, insulin resistance, dyslipideamia and lower adjusted metabolic rate [36,37]. Conversely, other studies did not describe any correlation between UCP2 45-bp I/D polymorphism and obesity [38,39].…”
Section: Discussionmentioning
confidence: 99%